The traditional maximal lactate steady state test versus the 5×2000 m test - Legaz-Arrese, A.; Carranza-Garcia, L. E.; Serrano-Ostariz, E.; Gonzalez-Rave, J. M.; Terrados, N. (International Journal of Sports Medicine, 2011)
Here, we compared the maximal lactate steady state velocity (vMLSS) estimated from a single-visit protocol (v5×2000) to the traditional multi-day protocol (vMLSS). Furthermore, we determined whether there was a lactate steady state during the time limits (Tlim) at vMLSS or v5×2000. Eight runners completed a half marathon (HM), the traditional protocol to determine the vMLSS and the 5×2000 m test in a randomised order, and a Tlim at vMLSS and at v5×2000 in a randomised order. The vMLSS (13.56±0.90 km·h - 1) was higher than the v5×2000 (12.93±0.90 km·h - 1, p=0.001) and comparable to the vHM (13.34±0.75 km·h - 1). The vMLSS (r=0.83) and the v5×2000 (r=0.91) were associated with the vHM but were not indicative of the competition pace. The Tlim at vMLSS (64±15 min) was lower than the Tlim at v5×2000 (94±21 min) and the HM time (95±5 min). In both Tlim, lactate was lower at 45 min than upon finishing the effort and was predictive of its duration (p<0.05). Our results indicate that the 5×2000 m test can be equally useful to assess runners as the traditional MLSS protocol and that there is no lactate steady state during the Tlim at vMLSS or at v5×2000.